Efficiency of fiscal policy stabilization measures in European Union countries - Maja Marjanović; Marina orević (Economic Themes, 2024)
For decades, macroeconomists have analyzed the role of fiscal policy in stabilizing economic trends in theory and practice. However, there is no general consensus on the efficiency of fiscal policy in stabilizing economic flows. Historically, fiscal policy has generally been considered stabilizing, but its flexibility in modern conditions can also have a developmental effect on the specific national economy. Macroeconomic instability can be caused by various shocks. First of all, this paper will discuss the basic postulates of stabilization fiscal policy in modern conditions and the macroeconomic signals of when and how to initiate stabilization through fiscal policy. It will also address the perennial dilemma of the effectiveness of automatic stabilizers versus discretionary fiscal policy measures for stabilization purposes. The essence of the paper is the analysis of the efficiency of fiscal policy stabilization measures in European Union countries, specifically the effects of public revenues and public expenditures on the output gap of the EU countries.
Keywords: E62; 330; fiscal policy; stabilization; The European Union